2020
DOI: 10.7759/cureus.9782
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Risk of Getting Peripheral Artery Disease in Rheumatoid Arthritis and the Selection of Appropriate Diagnostic Methods

Abstract: This study aims to review the evidence regarding the association between peripheral artery disease (PAD) and rheumatoid arthritis (RA), as well as influential underlying factors and diagnostic options. Eligible literature was searched in PubMed published up to June 1, 2020, in English. Case studies, case series, reviews, and meta-analyses were excluded. We also excluded non-human studies and those 20 years and older. A total of 44 studies were finally incorporated in the narrative review. The results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The ultrasound method enables a non-invasive achievement of images that show specific aspects of the vascular system and changes that may appear early in RA development. This detailed evaluation of the vessels correlates with and is influenced by CV factors (traditional or non-traditional), so ultrasound examination may provide useful information regarding CVD risk stratification, contributing to optimal treatment [ 212 , 213 , 214 , 215 ].…”
Section: Assessing Cardiovascular Disease Risk In Rheumatoid Arthritismentioning
confidence: 99%
“…The ultrasound method enables a non-invasive achievement of images that show specific aspects of the vascular system and changes that may appear early in RA development. This detailed evaluation of the vessels correlates with and is influenced by CV factors (traditional or non-traditional), so ultrasound examination may provide useful information regarding CVD risk stratification, contributing to optimal treatment [ 212 , 213 , 214 , 215 ].…”
Section: Assessing Cardiovascular Disease Risk In Rheumatoid Arthritismentioning
confidence: 99%
“…Machine learning-based models are also able to leverage on (non-causal or not) genetic variants to help reveal missing heritability and epistatic interactions on GWAS-based datasets 69 . Indeed, we also demonstrate that the proposed methodology identifies true biological signal by being able to recover clinically relevant disease relationships such as cancer and vitiligo 29,30 , Type II Diabetes and Alzheimer's disease [32][33][34][35][36][37] , and Rheumatoid arthritis and PAD [54][55][56][57][58] . Furthermore, previous studies 63,70 identified predictions that leverage GWASbased variants and further validated observations with experimental and clinical data.…”
Section: Discussionmentioning
confidence: 67%
“…Our network also showed novel edges connecting rheumatoid arthritis (RA) to PAD and glomerular filtration rate (GFR). Previous studies have highlighted supporting evidence of the association between RA and GFR 52,53 and RA and PAD [54][55][56][57][58] . Indeed, RA has pathological processes that also occurs in atherosclerosis, such as endothelial activation, inflammatory cell infiltration, neovascularization, and collagen degradation 59 .…”
Section: Figurementioning
confidence: 86%
See 1 more Smart Citation
“…This is extremely useful for screening patients at high cardiovascular risk, as elevated cIMT (≥1 mm) is correlated with the risk of acute cardiovascular events such as stroke or MI [ 13 , 132 ]. Studies have demonstrated strong predictive value for cardio- and cerebrovascular complications, as well as close links with most traditional cardiovascular risk factors, inflammatory syndrome, and hyperhomocysteinemia [ 13 , 133 , 134 , 135 ]. Doppler ultrasound of the carotid arteries also highlights the presence of atheromatous plaques, as well as the degree of stenosis that they produce.…”
Section: Assessing Cardiovascular Risk In Ramentioning
confidence: 99%